Unnecessary Investigations in Environmental Medicine - Greiner, Annette; Drexler, Hans (Deutsches Ärzteblatt international, 2016)
Patients in environmental medicine often want a thorough diagnostic evaluation of nonspecific symptoms. Unconventional testing, as well as conventional testing for indications other than the established ones, can lead to false diagnoses and, in turn, to substantial emotional, social, and financial harm. The goal of this single-center study was to assess inappropriate diagnostic testing among the patients of a specialized university outpatient clinic for environmental medicine.The charts of 653 consecutive outpatients seen in the institute and outpatient clinic of occupational, social, and environmental medicine in Erlangen from 2010 to 2015 were evaluated, and inappropriate diagnostic tests were assessed.9% of the patients had received at least one inappropriate diagnostic test. The most common one was an inappropriate heavy-metal test (26%), followed by an inappropriately ordered hair analysis (15%) and biomonitoring in the blood or urine with an erroneous choice of the testing matrix or an erroneous interpretation of the findings (15%). Biomonitoring performed by us did not confirm the suspected environmental diagnosis in any case. Laboratory values exceeding the normal limits were rarer among these patients than in the patients for whom we considered biomonitoring to be indicated without any pretesting.An appreciable number of patients in environmental medicine were subjected to inappropriate diagnostic testing. When this happens, proper testing often needs to be done thereafter in order to confirm or refute the findings. This phenomenon should be more thoroughly assessed and quantified.
EVALuna2:9755